Internet connectivity disruption in Guinea (Guinea) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Guinea. Data sourced from IODA.
Network Disruption Incident ID: GN-2026-0007. Severity: critical. Confidence: 65%